(untitled) (mathematica didactica, 2022)
The quality of classroom instruction is a major predictor for students’ learning development. Current research distinguishes three basic dimensions of teaching quality: (1) classroom management, (2) student support, and (3) cognitive activation. The focus of this paper is to investigate the relationship between the students’ perception of the teaching quality and their situational and individual interest in Mathematics education. The analyses are based on data taken from the SIGMA-Study, in which n = 940 8th grade students (‘Gymnasium’) are surveyed immediately after an introductory lessen on ‘equations of linear functions’.